Corrigendum: Modification of Barley Plant Productivity Through Regulation of Cytokinin Content by Reverse-Genetics Approaches - Holubová, Katarína; Hensel, Goetz; Vojta, Petr; Tarkowski, Petr; Bergougnoux, Véronique; Galuszka, Petr (Frontiers in plant science, 2018)
[This corrects the article DOI: 10.3389/fpls.2018.01676.].
Keywords: CRISPR-Cas9; yield; cytokinin; barley; silencing